Agricultural entrepreneurship and the financial crisis. (6th March 2019) - Dias, Cláudia S.L.; Rodrigues, Ricardo Gouveia
This paper aims to analyse the changes on the profile of the European agricultural entrepreneurs after the recent financial crisis, that began in 2008, given the impact of the crisis on European economic activity and the lack of studies on agricultural entrepreneurship. Using individual-level data from the total early-stage entrepreneurial activity for the European agricultural sector in 2007 (before the crisis) and 2012 (after the crisis), taken from the global entrepreneurship monitor, we investigate if after the crisis changes the role of motive, demographic and economic factors (gender, age, education, household income), perceived characteristics (opportunity perception, self-confidence, fear of failure, meeting other entrepreneurs) and innovativeness (clients, technology, competition). This study includes 22 European countries and the results allow us to conclude that the role of these variables is changed by the crisis, except for the role of gender, to meet other entrepreneurs, customers and competition, which may reflect specific characteristics of the agricultural sector.